1977
DOI: 10.1111/j.1471-0528.1977.tb12659.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Plasma Diazepam Levels in Mother and Infant

Abstract: Summary A 10 mg dose of diazepam was given intravenously to mothers at 15 to 205 minutes before delivery, and plasma diazepam concentrations were measured by gas‐liquid chromatography in mothers and infants at delivery and again 24 hours later. The plasma levels in the infants were always significantly higher than in the mothers but there was no evidence to suggest that the newborn were unable to metabolize the drug. All infants had a good Apgar score at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…One reason for the adverse effects observed in the neonates may be that, following maternal administration of D, the total concentrations of D and DD in the umbilical cord blood can exceed those in maternal blood (Idanpaan-Heikkila et al, 1971; Gamble et al, 1977;Kanto et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the adverse effects observed in the neonates may be that, following maternal administration of D, the total concentrations of D and DD in the umbilical cord blood can exceed those in maternal blood (Idanpaan-Heikkila et al, 1971; Gamble et al, 1977;Kanto et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…The drug may persist in the circulation of the neonate for up to 1 week (Gamble et al, 1977). In non-pregnant women, circulating diazepam is largely bound to albumin (Klotz et al, 1975;Kaplan, 1980) and is metabolised in the liver (Klotz et al, 1976).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Diazepam is one of the most commonly prescribed drugs in the management of pre-eclampsia and eclampsia: A number of studies have indicated that it can rapidly cross the placenta (Mandelli et al, 1975;Mirkin & Singh, 1976;Haram & Bakke, 1980) and reach steady-state concentrations in the foetus similar to (Cree et al, 1973) or higher (Gamble et al, 1977) than in the mother. The drug may persist in the circulation of the neonate for up to 1 week (Gamble et al, 1977).…”
Section: Introduction Methodsmentioning
confidence: 99%